(untitled) (The Journal of Psychology and Sociology, 2025)
The study focuses on interpreting the evolution of the scientific discourse on subjective well-being and happiness within an increasingly complex social reality, where individuals’ experienced quality of life becomes an indicator of sustainable development. The growth of publication activity and the expansion of interdisciplinary connections have created the need to systematize accumulated knowledge and identify major global trends. The aim of the study was to conduct a comprehensive bibliometric analysis of global publications on subjective well-being from 2001 to 2024, which made it possible to determine the developmental directions of theoretical and empirical research. The objectives included analysing publication dynamics, identifying leading countries, authors and journals, and reconstructing the conceptual structures of the field. The scientific significance lies in the fact that the revealed trends clarify the theoretical foundations of studying subjective well-being and highlight gaps such as the underrepresentation of Central Asia in international scholarship. The methodology included bibliometric analysis of 496 Scopus-indexed articles using the Bibliometrix R package, enabling the construction of citation networks, thematic clusters and publication dynamics. The findings demonstrate a steady increase in research interest and the dominance of studies originating from the United States, the United Kingdom and Western Europe. The conceptual structure comprises four core clusters: psychological mechanisms of well-being, socio-economic and health-related determinants, macroeconomic factors, and demographic-psychological aspects. The practical significance is reflected in the potential use of the results for developing regional assessment tools and adapting international measurement methodologies to the socio-cultural context of Central Asia. Keywords: subjective well-being, happiness, bibliometric analysis, research trends, Scopus database, global collaboration, conceptual framework.